Model Construction for Far Field Eddy Current Examination Simulation on Ferromagnetic Tubes. Issue 1 (August 2021) - Du, Haoyang; Yang, Zhou; Cui, Lun; Xiao, Huixu
Abstract: Ferromagnetic tubes are widely applied in fossil power plants such as waterfall tubes, overheat tubes or reheating tubes. Outer surface corrosion, wearing, depth reduction, cracks are common defects during manufacturing and long term operation. Eddy current detection is a traditional method for the examination of surface and near surface defects. However the efficiency is restricted by lift-off effect and skim effect. Far field eddy current overcomes the above disadvantages with high efficiency and fast examination speed and high sensitivity. In this paper, numerical simulation has been carried out to study the far field eddy current Detection for defects in small diameter ferromagnetic tubes in fossil power plants.